Some aspects of the actibities of the Kazakh intelligentsia in the Jadid movement in Kazakhstan (Journal of history, 2021)
Today, in the history of Kazakhstan, interest in the problems of the late 19th – early 20th centuries is growing. In this regard, the study of some aspects of the enlightenment movement of Jadidism, in particular the activities of the Kazakh intelligentsia in the struggle against the spiritual colonization of Tsarist Russia by reforming the public education system, determines the relevance of this study. In general, in the post-Soviet space, supporters of Jadidism, using the achievements of education and science of the period under study, strove to reform the system of public education and the formation of national ideas, which prompted the activation of the Kazakh intelligentsia. Jadidism as a new form of struggle against colonization received support in the steppe, where new-method schools were opened through charitable funding of the Turkic-Muslim intelligentsia. Involvement of previously unused archival materials in scientific circulation, their testing and comparative analysis with ingrained concepts in Soviet historiography laid the foundation for the methodological approach. Despite the diversity of views on the activities of the Kazakh intelligentsia, opposing the colonial oppression and the study of the problems of preserving national unity, this article puts forward the theoretical and methodological aspects of the regional features of the Jadid movement. The relevance of the study lies in the poorly studied issues of the formation of Kazakh intelligence in new-method schools in the second half of the 19th – early 20th centuries. in the Kazakh steppe and their role on the path of national self-preservation. The problems of the Jadid movement in Kazakhstan are of particular importance in the history of public education at the end of the 19th – beginning of the 20th centuries. and has not been sufficiently studied under the pressure of Soviet ideology. When studying archival materials, in particular the reports of the tsarist administration on the educational activities of the Kazakh intelligentsia, it can be concluded that the reforms of Jadidism covered not only the old-method mektebs and madrassas, but the learning process itself, as well as issues related to the formation of national-political ideas aimed at unity and self-preservation. In addition to the Jadid schools, through the efforts of the Kazakh intelligentsia, printing houses and libraries were opened in Kazakh cities and remote places, printing business developed, and work in the field of the native language and literature intensified. Thus, a comprehensive study of the activities of the Kazakh intelligentsia and the promotion of new ideas based on national interests, the movement of Jadidism in the Kazakh steppe in the second half of the 19th – early 20th centuries received a new impetus to the threatening colonial policy of the Russian Empire as a whole. Key words: Kazakhstan, Jadid movement, Kazakh intelligentsia, regional peculiarity.